Investigação da frequência alélica dos principais sistemas de grupos sanguíneos eritrocitários em doadores de sangue do Estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The identification of erythrocyte antigens is necessary in transfusion practice. The limitations of serological techniques for phenotyping have been overcome with the use of genotyping to identify variant alleles in genes corresponding to expression of erythrocyte antigens. Aiming at increasing transfusion safety of patients, the Ministry of Health has structured the erythrocyte genotyping service in different regions of Brazil to foster the national registry of rare bloods. The objectives of this study were to describe the allelic frequency of the Rh, Kell, Duffy, Kidd, MNS, Lutheran, Dombrock, Landsteiner-Wiener, Diego, Colton, and Sciana systems; to detect rare genotypes among blood donors in the State of Amazonas; and to identify the genotype frequencies that characterize the donors seen at the Amazonas Hospital Foundation for Hematology and Hemotherapy (HEMOAM). The allelic and genotypic frequencies for Rh, Kell, Duffy, Kidd, MNS, Lutheran, Dombrock, Landsteiner-Wiener, Diego, Colton and Sciana systems were analyzed by the MicroArray method, which detects 24 polymorphisms (SNPs) associated with 38 erythrocyte antigens and phenotypic variants in a single Multiplex PCR test, by means of on-chip probes. For RHCE genotyping a frequency of 0.103 was observed for possible VS+V+ and 0.009 for VS+V- phenotypes and that may be related to partial "c" and partial "e" antigens. Rare genotypes were found for DI*01/DI*01 (0.002), genotypes of low population frequency and important transfusion relevance, KEL*06/KEL*06 (0.001), LU*01/LU*01 (0.001) and for SC*02/SC*02 (0.002). The genotype frequencies RHCE*C/C (0.296), RHCE*C/c (0.248), RHCE*E/E (0.086), FY*A/FY*A (0.299), JK*B/JK*B (0.295) and DI*01/DI*02 (0.096) were different from genotyping performed in other states of Brazil and are characterized as a differential in relation to the genotype frequency of individuals in the Amazon region.
Keywords: Genética; Hematologia; Polimorfismo (Genética); CIENCIAS BIOLOGICAS: IMUNOLOGIA; Genotipagem; Genótipos variantes; Antígenos eritrocitários; Polimorfismo